Folkelige og sociale bevægelser. Nyere forskningsretninger og kvalitative forståelser - Wåhlin, Vagn (Grundtvig-Studier, 2003)
Folkelige og sociale bevagelser. Nyere forskningsretninger og kvalitative forstaelser [Popular and Social Movements. Recent Research Approaches and Qualitative Interpretations] By Vagn Wahlin However fascinating Grundtvig himself is as a central figure in 19th century Denmark, we, the citizens of the Third Millennium, have to ask why and how he is also interesting today and how his word, work and influence spread. Part of the answer to that fundamental question lies in the fact that he was the right man at the right place at the right time, with the right tidings to tell some clergymen and many peasant farmers on their dominant, middle size, family farms that they were the core of the nation. But part of the answer is to be found in the fact that his followers managed to elevate him to the influencing position as an inspirer and prophet of a broad popular movement that lasted for generations after his death. This popular, national and Christian movement of the Grundtvigians interacted in the social and political development of more than a hundred years with the other broad popular and ideological movements of Denmark such as the Labour Movement, the more Evangelical movement of the Home Mission, the Temperance movements, the Suffragists and women’s organizations, the associations of the world of sport, the political and youth organizations, etc. They were all active on the local level and soon also on the national level and, from the 1880s and onwards, established more firm organizations and institutions to deal with practical matters such as schools, boy scouts, community houses, soccer stadiums, magazines, newspapers, political associations, trade unions, as well as organized economic and anticapitalistic activities by co-operative dairies, breweries, slaughterhouses, export companies etc. As long as the agrarian sector of society (until around 1960-1970) dominated the national export to pay for the large import of society, that pattern of popular movements, also in the urban industry, influenced most of Danish history and life - and is still most influential in today’s post-modern society. During absolutism (1660-1848), organized social activities and associations were forbidden or strictly controlled. Yet a growing and organized public debate appeared in Copenhagen in late 18th century, followed by literary and semi-political associations amongst the enlightened, urban bourgeoisie. Around 1840 the liberals had organized themselves into urban associations and through newspapers. They were ready to take over the power of the society and the state, but could only do so through an alliance with the peasant farmers in 1846 followed by the German uprising in 1848 by the liberals in Schleswig-Holstein. In Denmark there existed a rather distinct dividing line - economic, cultural, social and in terms of political power - between two dominant sectors of society: Copenhagen, totally dominant in the urban sector, in contrast to the agrarian world, where 80% of the population lived. In the urban as well as in the agrarian sectors of society, the movements mostly appeared to be a local protest against some modernization or innovative introductions felt as a threat to religious or material interests - except for a few cases, where the state wanted an enlightened debate as in the Royal Agrarian Society of 1769. Whether the said local protesters won or lost, their self organization in the matter could lead to a higher degree of civil activity, which again could lead to the spread of their viewpoints and models of early organization. The introduction of civil liberties by the Constitution of 1849 made it more easy and acceptable for the broad masses of society to organize. However, with the spread of organizations and their institutions in the latter part of the 19th century, an ethical and social understanding arose that the power of the organized citizens should be extended from the special or vested interests of the founding group to the benefit of the whole of society and of all classes. So everybody who contributes positively, little or much, to the upholding and development of Danish society should be benefited and embraced by the popular movements. Around 1925 the Labour Movement as the last and largest in number and very influential had finally accepted that ethical point of view and left the older understanding of the suppressed army of toiling and hungry workers. The people, the ‘folk’, and the country of all classes had then been united into ‘Danmark for folket’ (a Denmark o f by and fo r the people). So while a social movement may be an organization of mere protest or vested interests or a short-lived phenomena, a ‘folkelig bevagelse’ (popular movement) became what it was at first - in the understanding of the majority of the Danes, but not in the eyes of the 19th century bourgeois and landowner elite - a positive label. It is still so today, though it is now questioned by many of the more internationally-minded members of the new elite. The word ‘folk’ in the term ‘folkelig bevagelse’ is so highly valued that nearly all political parties of today have included it in their names. For the majority of people, Danish and popular and movements stand for the organized societal activity of those who accept the language, history, culture including religion, landscapes, national symbols, etc. of Denmark and who incorporate all this as a valid part of their self-understanding just as they actively take part in the mutual responsibility for their fellow countrymen. This general attitude is most clearly demonstrated when it is severely breached by some individual or group. With the addition of the Church and the Christian dimension, we have what is the essence of Grundtvig’s heritage. Without this source of inspiration, the popular movements up to a generation ago would have been different and perhaps of less importance, and without the popular movements, Grundtvig’s influence would have been less important in Denmark of the last hundred years. We may best understand this as a process of mutual dependency and of a mutual societal interaction.